Structural and Optical Properties of Novel In(2)O(3) Nanoparticle-Assembled Nanorods - Lai, Hsiang-Yu; Chen, Chun-Hua; Lee, Chi-Feng (My University, 2010)
In(2)O(3) nanoparticle-assembled nanorods with distinct surface morphologies have been newly synthesized by a dehydration process of self-assembled In(OH)(3) nanorods obtained from a liquid-based route. The reaction mechanism and the structural transformation between these two one-dimensional nanorods, In(2)O(3) and In(OH)(3), were precisely characterized by means of various qualitative and quantitative analyses with X-ray scattering simulations. The broad absorption band in the UV-visible spectrum evidently originates from the nanoparticle-assembling effect within the In(2)O(3) nanorods. An intensive photoluminescence emission at 440 nm observed under an excitation wavelength of 325 nm is attributed to the existence of oxygen vacancies within the In(2)O(3) nanorods.